Variabilidade espaço-temporal das disponibilidades eólica, hídrica e solar no estado do Paraná, Brasil - Guicho, Ricardo (2023)
The insertion of renewable sources in the electricity matrix has been addressed with greater frequency, justified mainly due to the worsening of environmental issues coupled with the growth in demand. However, they are intermittent sources and require planning to ensure reliability and minimize the costs of electricity generation. This work aims to understand the behavior and evaluate the complementarity of wind, photovoltaic and hydro resources in the state of Paraná, southern Brazil. For this purpose, wind speed and direction, solar irradiation, and rainfall data were collected from 57 SIMEPAR weather stations throughout the state. In cases where gaps were detected in the database records, filling was performed with the regional weighting method. Descriptive statistics were performed according to the period of the analyses (monthly and seasonal) and the variables of wind speed, irradiation and rainfall. To identify the influence of space and time factors on the averages of the availability variables of the three sources (wind speed, rainfall and irradiation), variance analysis was used. Thus, the dependence of the sources as a function of time and space was evaluated. For the spatialization of the results, the results of monthly and seasonal averages were used together with longitude and latitude information to perform kriging. These values were represented by thematic maps, prepared in QGis, divided into classes according to the variables analyzed. With the results of kriging and programming language in the ArcQGis software, it was possible to generate roses of complementarity as a function of distance and availability of climate variables and then understand, for each of the sources, the behavior and occurrences throughout the year, by monthly and seasonal analysis in the ten mesoregions of the state of Paraná. The results were presented by clusters of pairs, the wind-solar configuration presents mapping with high rates of complementarity for Northwest, West and Southwest as a function of several mesoregions. When considering the wind-hydric variation only the Center-South and Southeast Paraná do not present high indices. For the hydro-solar configuration the South-Central and Southeast mesoregions indicate high or very high complementarity for all the other mesoregions.